Effectiveness of maternal vaccination with quadrivalent inactivated influenza vaccine in pregnant women and their infants in 2019-2020. (3rd July 2022) - Maltezou, Helena C.; Stavros, Sofoklis; Asimakopoulos, George; Pergialiotis, Vasilios; Raftopoulos, Vasilios; Talias, Michael A.; Pavli, Androula; Daskalakis, George; Sindos, Michael; Koutroumanis, Pelopidas; Theodora, Marianna; Antsaklis, Panagiotis; et al.
ABSTRACT: Objectives: Influenza is associated with an increased risk for serious illness, hospitalization, and death in pregnant women and young infants. Our aim was to estimate the effectiveness of a quadrivalent inactivated influenza vaccine (QIV) in pregnant women and their infants during 2019–2020. Methods: A QIV vaccine was offered to pregnant women followed in a maternity hospital. Women were contacted weekly during the influenza season and asked about symptoms. Polymerase chain reaction testing in pharyngeal samples was offered to pregnant women and infants with influenza-like illness. A Bayesian beta-binomial model was used. Results: We studied 636 pregnant women (406 vaccinated and 230 unvaccinated) and 474 infants (281 of mothers vaccinated in pregnancy and 193 of unvaccinated mothers). Using a Bayesian beta-binomial model, it was estimated that influenza vaccination of pregnant women reduced their logit to develop laboratory-confirmed influenza by −4.2 (95% CI −3, 7 − 4, 7) and the logit of their infants to develop laboratory-confirmed influenza by −4.2 (95% CI −3.6, −4.9). The QIV effectiveness against laboratory-confirmed influenza was 43.5% in pregnant women and 31.4% in infants. Conclusion: Maternal influenza vaccination with QIV in pregnancy reduced the odds of pregnant women and their infants to develop influenza. Clinical trial registration: www.clinicaltrials.gov identifier is NCT04723771.